MODELING A MATRIX FOR FORMAL VERIFICATION (2009)
A reference model may be defined to refer to a matrix of a target computerized system. The reference model may comprise a reference index and a reference matrix. The reference index may have a non-deterministic value enabling the reference matrix to refer to the matrix using a fewer number of cells. The disclosed subject matter may enable a more efficient model checking process of a computerized device by using a reference model that is relatively easy to define or maintain or by using a reference model that is configured to be more efficient for model checking as it uses non-determinism.